Studies on adenosine triphosphate content in red blood cell and the trapping of red blood cell in the brain of monkeys infected with plasmodium knowlesi - Kalaya Thaijongrak (Chulalongkorn University, 2014)
Thesis (M.Eng.)--Chulalongkorn University, 1974